(3eNJUQ cJGH GdHjWQIs - (3CMeO Hf GdMSf Hf GdGMfas ((3Ydi Hf GdMSf Hf gHI Gddg s)
(3ChdgG (B:s
(3GdegQ Edi Cf JCJi SfI adh , hEfeG Sei adhkG dCfg jadi QhK Ceg ajCcd QbGbg hCgd GddZI jbhdhf (B: (3EfeG Sei adhkG dCfg adi Yf Ceg haWe Ke ai GdSfI GdKGfjI LQdi s
(3BNQgG (B:s
(3eHJhQ hBNQg GdHGH GdQGHY hGdYTQjf ai GdMcI hGdLQH hGdHQU hZjQg s
(3CQHY YTQI dhMI ef GdcJGHs
(3JeKd GdNjd eY ShGSgGs
(3hgj YHGQI Yf eLehYI UhQ ddNjhds
(3hJMJ cd UhQI JYdjb GdeDda YdjgG s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdWHs